SPADA Optimization Mentoring Program in Online Learning for Lecturers of FKIP Universitas Veteran Bangun Nusantara Sukoharjo - ahmad rosyid; Singgih Subiyantoro; M Arif Maulana (International Journal of Public Devotion, 2022)
This mentoring aims to provide the skills of teaching staff/lecturers in the FKIP Univet environment for compiling, designing and operating SPADA during online learning. This activity was carried out for 2 days which was divided into 4 sessions. In these activities, lecturers receive mentorinh starting from how to enter a list of lecture participants, provide introductions to courses, upload materials and arrange assignments, discussions and quizzes guided by the IT team of the University of Veteran Bangun Nusantara Sukoharjo. At the end of the activity, the lecturer is also given a video tutorial which can be accessed at any time when there are difficulties in operating the SPADA Univet. This activity was attended by 91 FKIP lecturers from 11 Study Programs, including those who had attended similar guidance, so that learning was partly integrated with SPADA Univet. It after participating in this mentoring activity, there be an increase 80,2 %, and lecturers will be able to integrate every lesson into SPADA Univet.